Gas pressure and coating distance for nanohydroxyapatite deposition on stainless steel 316L using flame spray technique - SAPUTRA, Angga; SYAFITRI, Utami Dyah; SUDIRO, Toto; TIMUDA, Gerald Ensang; SARI, Yessie Widya (Journal of Metals, Materials and Minerals, 2021)
Metal implant coating engineering is needed to improve the surface biocompatibility properties of metals. For this, coating metal surfaces with bioactive and biocompatible biomaterials will be an option. Having high biocompatibility as well as similarity in chemical properties, nanohydroxyapatite may be a candidate as biomaterials for coating the metal implant. The key to the success of metal implant plating is the formation of pores which increase the bioactivity and biocompatibility properties of the implant. In this study, nanohydroxyapatite was used to be coated on stainless steel type 316L (SS316L). To ensure that the coating works properly on the surface, an appropriate measure of gas and distance is required. The purpose of this study was to determine the possible firing distance and gas pressure of the flame spray coating technique. The X-ray diffractometer (XRD), scanning electron microscope - energy dispersive X-ray spectroscopy (SEM-EDS), and optical microscopy (OM) characterizations were carried out to determine the phase, morphology, and presence of pores. After coated product, hydroxyapatite dehydroxylation occurred which led to the tetracalcium phosphate (TTCP) and β-tricalcium phosphate (β-TCP) phases. The thickness decreases with the addition of gas pressure and the farther the firing distance the layer thickness decreases. Nanohydroxyapatite coating on a bone implant substrate can increase the porosity of the layer.